Cultivating Compassion How Digital Storytelling is Transforming Healthcare (Springer International Publishing, 2018)
This book explores how digital storytelling can catalyze change in healthcare. Edited by the co-founders of the award-winning Patient Voices Programme, the authors discuss various applications for this technique; from using digital storytelling as a reflective process, to the use of digital stories in augmenting quantitative data. Through six main sections this second edition covers areas including healthcare education, patient engagement, quality improvement and the use of digital storytelling research. The chapters illuminate how digital storytelling can lead to greater humanity, understanding and, ultimately, compassion. This collection will appeal to those involved in delivering, managing or receiving healthcare and healthcare education and research, as well as people interested in digital storytelling and participatory media.